Lack of serological and molecular evidence of arbovirus infections in bats from Brazil - Bittar, Cíntia [UNESP]; Machado, Rafael R.G. [UNESP]; Comelis, Manuela T. [UNESP]; Bueno, Larissa M. [UNESP]; Morielle-Versute, Eliana [UNESP]; Beguelini, Matheus R. [UNESP]; De Souza, Renato P.; Nogueira, Maurício L.; Rahal, Paula [UNESP] (Public Library of Science (PLoS), 2018)
Viruses are important agents of emerging zoonoses and are a substantial public health issue. Among emerging viruses, an important group are arboviruses, which are characterized by being maintained in nature in cycles involving hematophagous arthropod vectors and a wide range of vertebrate hosts. Recently, bats have received increasing attention as an important source for the emergence of zoonoses and as possible viral reservoirs. Among the arboviruses, there are many representatives of the genera Flavivirus and Alphavirus, which are responsible for important epidemics such as Dengue virus, Zika virus and Chikungunya virus. Due to the importance of analyzing potential viral reservoirs for zoonosis control and expanding our knowledge of bat viruses, this study aimed to investigate the presence of viruses of the Alphavirus and Flavivirus genera in bats. We analyzed serum, liver, lungs and intestine from 103 bats sampled in northeast and southern Brazil via Nested-PCR and the hemagglutination inhibition test. All samples tested in this study were negative for arboviruses, suggesting that no active or past infection was present in the captured bats. These data indicate that the bats examined herein probably do not constitute a reservoir for these viruses in the studied areas. Further studies are needed to clarify the role of bats as reservoirs and sources of infection of these viral zoonoses.